(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Addiction medicine is a medical specialty that deals with the treatment of addiction. The specialty often crosses over into other areas, since various aspects of addiction fall within the fields of public health, psychology, social work, mental health counseling, psychiatry, and internal medicine, among others. Incorporated within the specialty are the processes of detoxification, rehabilitation, harm reduction, abstinence-based treatment, individual and group therapies, oversight of halfway houses, treatment of withdrawal-related symptoms, acute intervention, and long term therapies designed to reduce likelihood of relapse. Some specialists, primarily those who also have expertise in family medicine or internal medicine, also provide treatment for disease states commonly associated with substance use, such as hepatitis and HIV infection. Physicians specializing in the field are in general agreement concerning applicability of treatment to those with addiction to drugs, such as alcohol and heroin, and often also to gambling, which has similar characteristics and has been well-described in the scientific literature.There is less agreement concerning definition or treatment of other so-called addictive behavior such as sexual addiction and internet addiction, such behaviors not being marked generally by physiologic tolerance or withdrawal.Doctors focusing on addiction medicine are medical specialists who focus on addictive disease and have had special study and training focusing on the prevention and treatment of such diseases. There are two routes to specialization in the addiction field one via a psychiatric pathway and one via other fields of medicine.The American Society of Addiction Medicine notes that approximately 40 of its members are psychiatrists (MDDO) while the remainder has received primary medical training in other fields.